การศึกษาจลนศาสตร์การอบแห้งเนื้อหมูด้วยเครื่องอบแห้งพลังงานแสงอาทิตย์ Drying Kinetics of Pork by Using Solar Dryer - ดวงพร ศิริ (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2016)
บทคัดย่อ การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อศึกษาจลนศาสตร์การอบแห้งของเนื้อหมูที่อบด้วยเครื่องอบแห้ง พลังงานแสงอาทิตยแ์ ละการตากแดด และศึกษาประสิทธิภาพเชิงความรอ้ นของระบบอบแหง้ ดว้ ยเครื่องอบแหง้ พลังงานแสงอาทิตย์ โดยใช้เนื้อหมู ขนาด 5 × 3 × 1 ซม. จำนวน 2 กิโลกรัม ความชื้นเริ่มต้น 254 %d.b. อบในเครื่องอบแห้งพลังงานแสงอาทิตย์ และตาดแดด จนกระทั่งมีความชื้นสุดท้ายเท่ากับ 70 %d.b. ทำการทดลองในช่วงเวลา 09.00 - 16.00 น. ผลการวิจัยพบว่า ความชื้นและอัตราความชื้นของเนื้อหมู ที่อบด้วยเครื่องอบแห้งพลังงานแสงอาทิตย์จะลดลงเร็วกว่าการตากแดด โดยที่เครื่องอบแห้งพลังงาน แสงอาทิตย์ใช้เวลาในการอบแห้ง 330 นาที ส่วนการตากแดดใช้เวลา 360 นาที เครื่องอบแห้งพลังงาน แสงอาทิตย์มีประสิทธิภาพเชิงความร้อนของระบบในการอบแห้งเนื้อหมูสูงกว่าการตากแดด Abstract This research aimed to investigate the drying kinetics of pork using solar dryer and open sun drying and the thermal efficiency of solar dryer. The solar dryer and open sun drying were the experiment equipment. A 2 kg pork with a dimension of 5 × 3 × 1 cm., with the initial moisture content of 254 %d.b. were dried by using solar dryer and open sun drying, to a final moisture content of 70 %d.b.. The results of this study showed that the moisture content and moisture rate of pork drying using solar dryer was faster than the open sun drying. The drying time for each drying method were 330 and 360 minutes, respectively. The thermal efficiency of the solar dryer for pork drying is higher than open sun drying.